Gender Empowerment Through Politics in the Classroom: D6.8 Working Paper 1 - Abendschön, Simone; García-Albacete, Gema; Alonso, Maria; Kleer, Philipp; Núñez, Lidia; Sánchez, David; Justus Liebig University Giessen (My University, 2025)
While we can observe notable progress toward gender equality in Europe, significant gender disparities in political engagement persists across countries and over time. The G-EPIC project addresses gendered political inequality from an intersectional perspective. Working Package 2 (WP2) contributed to a thorough understanding of the origins of gendered inequalities in political attitudes and behaviour, focusing on political interest and internal political efficacy as key contributors to political participation. Our work could update previous knowledge regarding the origins and long-term effects of socioeconomic inequalities on political engagement, while exploring the intersections of various factors such as gender, socioeconomic status, and immigration background. Based on existing studies, a systematic literature review and new analyses using international survey data, our analyses reveal a persistent gender gap in political interest and internal political efficacy, observable from adolescence into adulthood. While men's internal political efficacy tends to grow over time, women's remains stable, contributing to long-term disparities. Moreover, the systematic analysis of existing studies showed that sources of inequalities (gender, socioeconomic status or ethnicity/origin) were mostly treated separately, shadowing (covering?) possible interaction effects between these. A further key limitation of this research area is the lack of panel data available to study socialization processes, the long-term effects of early inequalities, and studies focusing on disadvantaged populations. Our own analyses, among others, addressed this gap and examined different intersectional effects, recently published in two papers (https://doi.org/10.17645/pag.9286, https://doi.org/10.17645/pag.9309). We uncovered preliminary evidence of a positive intersectional effect of being a girl and having an immigration background on levels of political interest among adolescents. However, this does not mean that girls with immigration backgrounds have higher levels of interest than any other group. However, it does imply that they have higher levels of political interest than we could expect by adding the impact of being a girl and having an immigrant background on their own. Regarding political participation, our analyses demonstrated that women participate more in non-institutional forms of participation, while men participate more in institutional ones. Applying an intersectional approach, women not born in the country are the least likely to participate in non-institutional forms of participation, whereas having foreign parents boosts some actions. Additionally, we explored the potential effect of discrimination experiences on political involvement, discovering that perceived discrimination leads to higher levels of political interest. Contradicting our expectations, we did not encounter a significant interaction effect between discrimination experiences and social participation, indicating that the level of discrimination experience does not moderate the impact of social participation on political interest. The comprehensive analyses in WP2 emphasise the existing gender gap in different forms and provide first evidence of the complex intersectional dynamics between different social disadvantages. Hence, further addressing the intersection of sources of inequalities in political engagement and participation is an important venue for future research.
Keywords: youth; politial engagement; intersectionality; political participation; inequality